Vocational education and training in times of global crisis : a preliminary evaluation of the German Presidency of the EU Council - Himstedt, Julia [Verfasser]; Le Mouillour, Isabelle [Verfasser] (My University, 2021)
"Germany chaired the Council of the European Union from July to December 2020. Following the formation of the new EU Commission, one of the major tasks pursued during this period was to review the strategic framework for European cooperation in vocational education and training (“Europe 2020”) and to define fresh priorities for the next ten years. This article makes an initial assessment of how well this succeeded given the conditions imposed by the coronavirus pandemic." (authors' abstract; BIBB-Doku)
Berufsbildung in globalen Krisenzeiten : eine erste Bilanz der deutschen EU-Ratspräsidentschaft
Keywords: S 2.3 Berufsbildungspolitik; I 2.2 Europa; S 1.3 Berufliche Erstausbildung; 370; EU-Bildungspolitik; Berufsausbildung; Vorsitz im Rat der Europäischen Union; Weiterbildungsverhalten; Bildungspersonal; Chancengleichheit